Androgenetic alopecia in woman treated with botulinum toxin - Henny Wijaya; Ketut Kwartantaya Winaya (DiscoverSys Inc., 2021)
Background: Androgenetic alopecia (AGA) is the most common type of alopecia. AGA in women is called Female Pattern Hair Loss (FHPL). FHPL occurs in 50% of adolescence women. Case Description: A 29-year-old woman presented with hair thinning on the top of her head in the last 3 years. Dermatological status in the parietal region showed a diffuse and ill-define patch of alopecia, and hair thinning was found along the midline of the scalp. The hair pull test in frontal, temporal, and parietal regions was negative. The Severity of Alopecia Tool (SALT) score is 10, and patient belonged to stage 2 according to The Sinclair Scale. Dermoscopy examination revealed scattered white dots over the vertex of the scalp with various hair diameters. Miniaturized hair and vellus hair were found in several areas. The ratio of terminal to vellus hair was 20:6 or 3:1. Injection of 100-unit botulinum toxin in the alopecia area was done every 3 months. After 1 month of treatment, the hair thinning was reduced. Conclusion: Appropriate treatment will affect the prognosis of AGA patients. Appropriate treatment that based on the pathophysiology of the disease and the patient's genetics will provide a good therapeutic response.